2013
DOI: 10.1007/s13277-013-1508-2
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing analysis of BRCA1 methylation level in breast cancer cells

Abstract: BRCA1 and BRCA2 genes are crucial for double-strand break repair by homologous recombination, and mutations in these genes are responsible for most familial breast carcinomas. Cells with inactivating mutations of the BRCA1 or BRCA2 tumor suppressor genes are sensitive to poly (ADP-ribose) polymerase-1 (PARP1) inhibitors. Already in 2010, it has been predicted, that BRCA1 hypermethylation might be sensitive to PARP1 inhibitor. However, till today, a statistically significant proof has been missing, and the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Furthermore, several lines of evidences confirmed that the expression pattern of sporadic BRCA1 -methylated breast cancers was the same as that of inherited BRCA1 mutations 52 . Herein, numerous preclinical researches investigated whether the antitumor activity of DNA-damaging agents in BRCA1 -mutated breast cancers had a similar activity in BRCA1 -methylated tumors, and the results demonstrated that the BRCA1 hypermethylation conferred the same extent of sensitivity to poly adeno-sine diphosphate-ribose polymerase-1 (PARP1) inhibitors and platinum-derived drugs as did the BRCA1 mutation 53 54 55 . Moreover, Xu et al reported that BRCA1 -methylated triple-negative breast tumor patients were sensitive to adjuvant chemotherapy and had a significantly better 10-year disease-free survival (DFS) and disease-specific survival (DSS) than patients with BRCA1 -unmethylated triple-negative tumors 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several lines of evidences confirmed that the expression pattern of sporadic BRCA1 -methylated breast cancers was the same as that of inherited BRCA1 mutations 52 . Herein, numerous preclinical researches investigated whether the antitumor activity of DNA-damaging agents in BRCA1 -mutated breast cancers had a similar activity in BRCA1 -methylated tumors, and the results demonstrated that the BRCA1 hypermethylation conferred the same extent of sensitivity to poly adeno-sine diphosphate-ribose polymerase-1 (PARP1) inhibitors and platinum-derived drugs as did the BRCA1 mutation 53 54 55 . Moreover, Xu et al reported that BRCA1 -methylated triple-negative breast tumor patients were sensitive to adjuvant chemotherapy and had a significantly better 10-year disease-free survival (DFS) and disease-specific survival (DSS) than patients with BRCA1 -unmethylated triple-negative tumors 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, they used peripheral blood as diagnostic specimen for the determination of methylation status of BRCA1 promoter, which could be therefore used as a screening tool ( 41 ). Promoter hypermethylation of BRCA1 could serve also as predictive biomarker for PARP1 inhibitor therapy, which has been currently used only for treatment of patients with BRCA1 and BRCA2 mutations to decrease the growth and vascularisation of tumour ( 42 ). …”
Section: Breast Cancermentioning
confidence: 99%
“…BRCA1 promoter methylation has also been proposed as a marker for HR deficiency, as functional methylation of the BRCA1 promoter leads to repression of BRCA1 mRNA expression [55,56]. Specific assays to detect BRCA1 promoter methylation in clinical cancer samples, including tumor biopsies, have been developed and validated [57].…”
Section: Predictive Biomarkers For Parp Inhibitor Sensitivitymentioning
confidence: 99%